logo

Solution of the Laplace Equation Independent of Azimuthal Angle in Spherical Coordinates using the Method of Separation of Variables 📂Mathematical Physics

Solution of the Laplace Equation Independent of Azimuthal Angle in Spherical Coordinates using the Method of Separation of Variables

Theorem

The general solution of the Laplace’s equation with azimuthal symmetry in spherical coordinates is as follows:

V(r,θ)=l=0(Alrl+Blrl+1)Pl(cosθ) V(r,\theta) = \sum \limits_{l=0} ^\infty \left( A_{l} r^l + \dfrac{B_{l}}{r^{l+1} } \right) P_{l}(\cos \theta)

Proof

Step 0

When finding the potential in cases where the boundary condition is easily expressed in spherical coordinates, one must solve the Laplace’s equation for spherical coordinates. The Laplace’s equation in spherical coordinates is as follows. (ref, ref)

2V=1rr(r2Vr)+1r2sinθθ(sinθVθ)+1r2sin2θ2Vϕ2=0 \nabla ^2 V = \dfrac{1}{r} \dfrac{\partial}{\partial r} \left( r^2 \dfrac{\partial V}{\partial r} \right) +\dfrac{ 1}{r^2 \sin \theta } \dfrac{ \partial}{\partial \theta} \left( \sin \theta \dfrac{ \partial V}{\partial \theta }\right) + \dfrac{1}{r^2 \sin ^2 \theta} \dfrac{ \partial ^2 V}{\partial \phi^2 }=0

Let’s assume the potential VV is a function independent of ϕ\phi. In other words, when other values remain the same and only ϕ\phi changes, the value of VV does not change. Then, the change of VV with respect to ϕ\phi is 00, and this leads to Vϕ=0\dfrac{\partial V}{\partial \phi}=0, so the third term disappears.

1rr(r2Vr)+1r2sinθθ(sinθVθ)=0(1) \dfrac{1}{r} \dfrac{\partial}{\partial r} \left( r^2 \dfrac{ \partial V}{\partial r} \right) +\dfrac{ 1}{r^2 \sin \theta } \dfrac{ \partial}{\partial \theta} \left( \sin \theta \dfrac{ \partial V}{\partial \theta }\right)=0 \tag{1}

Let’s assume the potential V(r,θ)V(r, \theta) is a function that allows separation of variables. That means we assume VV is composed of the product of the function of rr alone R(r)R(r) and the function of θ\theta alone Θ(θ)\Theta (\theta) . Substitute V(r,θ)=R(r)Θ(θ)V(r,\theta)=R(r) \Theta (\theta) into (1)(1) and divide both sides by VV to simplify it as shown below.

1Rddr(r2dRdr)+1Θsinθddθ(sinθdΘdθ)=0 \dfrac{1}{R} \dfrac{d}{d r} \left( r^2 \dfrac{d R}{d r} \right) +\dfrac{ 1}{ \Theta \sin \theta } \dfrac{ d}{d \theta} \left( \sin \theta \dfrac{ d \Theta}{d \theta }\right) = 0

Since each term depends only on rr and θ\theta, both terms are constants. The value of the second term and the right side does not change even if rr changes. Therefore, the value of the first term must always be the same, which means it is a constant term. The second term is also a constant term for the same reason.

1Rddr(r2dRdr)=l(l+1) \dfrac{1}{R} \dfrac{d}{d r} \left( r^2 \dfrac{d R}{d r} \right) =l(l+1)

1Θsinθddθ(sinθdΘdθ)=l(l+1) \dfrac{ 1}{\Theta \sin \theta } \dfrac{d}{d \theta} \left( \sin \theta \dfrac{d \Theta }{d \theta }\right) = -l(l+1)

The complex partial differential equation of (1)(1) has been simplified into two ordinary differential equations. Solving each differential equation to find R(r)R(r) and Θ(θ)\Theta (\theta) and multiplying them yields the desired V(r,θ)V(r,\theta).

Step 1

ddr(r2dRdr)=l(l+1)R \dfrac{d}{dr} \left( r^2 \dfrac{dR}{dr} \right) = l(l+1) R     2rdRdr+r2d2Rdr2=l(l+1)R \implies 2r \dfrac{dR}{dr} +r^2 \dfrac{d^2 R}{dr^2} =l(l+1)R

    r2d2Rdr2+2rdRdrl(l+1)R=0\implies r^2 \dfrac{d^2 R}{dr^2} + 2r\dfrac{dR}{dr} - l(l+1)R=0

This takes the form of an Euler equation, and although the solution can be found here, this document will solve it in a simpler manner. Use the fact that the solution to the above differential equation comes out in the form of rkr^k and substitute R=rkR=r^k in the first line. Then,

ddr(r2drkdr)=l(l+1)rk \dfrac{ d}{dr} \left( r^2 \dfrac{ d r^k}{dr} \right) = l(l+1)r^k     ddr(krk+1)=l(l+1)rk \implies \dfrac{d}{dr} (k r^{k+1} ) = l(l+1) r^k     k(k+1)rk=l(l+1)rk \implies k(k+1)r^k=l(l+1)r^k k(k+1)=l(l+1) \therefore k(k+1)=l(l+1)     k2+kl(l+1)=0 \implies k^2+ k -l(l+1)=0

Using the quadratic formula, the solution is either k=lk=l or k=(l+1)k=-(l+1). Therefore, rlr^l and 1rl+1\dfrac{1}{r^{l+1} } are solutions to the differential equation. The general solution is a linear combination of the two solutions, so R(r)=Arl+Brl+1R(r)=Ar^l + \dfrac{B}{r^{l+1} }, A,BA,B are constants

Step 2

ddθ(sinθdΘdθ)=l(l+1)sinθΘ \dfrac{d}{d\theta} \left( \sin \theta \dfrac{d \Theta }{d \theta} \right) =-l(l+1)\sin \theta \Theta

The solution to the differential equation for θ\theta is complex, so only the result is introduced here. For a detailed solution, refer here. The solution to the above differential equation is the Legendre polynomial for cosθ\cos \theta .

Θ(θ)=Pl(cosθ) \Theta (\theta) = P_{l}( \cos \theta)

At this time, Pl(x)P_{l}(x) is as follows.

Rodrigues’ formula Pl(x):=12ll!(ddx)l(x21)l P_{l}(x) := \dfrac{1}{2^l l!} \left( \dfrac{d}{dx} \right) ^l (x^2-1)^l

l은양의정수,은 양의 정수, P_{0}(x)=1$

위 공식에 따라 계산한 르장드르 다항식은 아래와 같다.

P0(x)=1P_{0}(x) =1 P1(x)=xP_{1}(x)=x P2(x)=3x212P_2(x) = \dfrac{3x^2-1}{2} P3(x)=5x33x2P_{3}(x) = \dfrac{5x^3 -3x}{2} \vdots

2계 미분방정식이므로 2개의 해를 구해야하는데 각 ll 값에 대해 하나의 해만 있다. 나머지 두번째 해는 θ=0\theta=0θ=π\theta=\pi에서 발산하기 때문에 물리적인 의미가 있는 해가 아니다. 따라서 드장드르 다항식에 의한 첫번째 해만 고려해주면 된다.

단계 3.

단계 1단계 2 의 결과를 종합하면 전위는

V(r,θ)=(Arl++Brl+1)Pl(cosθ) V(r,\theta) =\left( Ar^l ++ \dfrac{B}{r^{l+1}} \right) P_{l}( \cos \theta)

이 때 각 ll Since there is a solution for each value, the general solution is the sum of all of these.

V(r,θ)=l=0(Alrl+Blrl+1)Pl(cosθ) V(r,\theta) = \sum \limits_{l=0} ^\infty \left( A_{l} r^l + \dfrac{B_{l}}{r^{l+1} } \right) P_{l}(\cos \theta)